Pengaruh Konflik Kerja, Stres Kerja dan Etos Kerja Terhadap Kinerja Pegawai Dinas Pendidikan dan Kebudayaan Kabupaten Bireuen - Muhammad, Teuku; Idris, Amiruddin; Win, Konadi (Singkite Journal, 2023)
In the work environment, things related to work conflicts often occur, the nuances of which are usually conflicts of interest, work misunderstandings or differences in ideas and innovation. Likewise, in the work environment, it is not uncommon for work stress to occur due to an inability to coordinate the management of work and tasks. Of course this will affect performance. Employees must continue to maintain their work ethic whatever the conditions and regulations, so that work results can run optimally. This issue is important to pay attention to. And in this case this research was carried out. With studies and research on employees of the Bireuen Regency Education and Culture Service. Namely the Bireuen government agency which has quite a large number of employees. The research was carried out descriptively associative with a quantitative approach, with analysis tools using path model statistics. The results of the research found several things, namely: (a) there is a relationship between the variables of work conflict, work stress and work ethic. (b) there is an influence of each of these variables on employee performance, namely the influence of the work conflict factor has a negative influence of 12.5%, the work stress factor also has a negative influence of 9,66% while the work ethic factor has a negative influence. provide a positive impact on employee performance. 53,096%. (c) Simultaneously work conflict, work stress and work ethic contribute 70,6% to the performance of Bireuen Regency Education and Culture Service employees